2021
DOI: 10.1038/s41392-021-00627-y
|View full text |Cite|
|
Sign up to set email alerts
|

M2 macrophages, but not M1 macrophages, support megakaryopoiesis by upregulating PI3K-AKT pathway activity

Abstract: Dysfunctional megakaryopoiesis hampers platelet production, which is closely associated with thrombocytopenia (PT). Macrophages (MФs) are crucial cellular components in the bone marrow (BM) microenvironment. However, the specific effects of M1 MФs or M2 MФs on regulating megakaryocytes (MKs) are largely unknown. In the current study, aberrant BM-M1/M2 MФ polarization, characterized by increased M1 MФs and decreased M2 MФs and accompanied by impaired megakaryopoiesis-supporting abilities, was found in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 52 publications
3
45
0
Order By: Relevance
“…The PI3K/AKT signaling pathway is at the core of T cell activation, and it acts downstream of the T cell activation signal [ 29 , 30 ]; its main function is to promote T cell glycolysis, and it plays a key role in regulating T cell differentiation and activity [ 31 , 32 ]. However, continuous activation of this pathway promotes terminal differentiation of T cells and loss of memory, which affects T cell function [ 33 ].…”
Section: Strategy For Optimizing Metabolism To Improve Efficacy During Car-t Cells Productionmentioning
confidence: 99%
“…The PI3K/AKT signaling pathway is at the core of T cell activation, and it acts downstream of the T cell activation signal [ 29 , 30 ]; its main function is to promote T cell glycolysis, and it plays a key role in regulating T cell differentiation and activity [ 31 , 32 ]. However, continuous activation of this pathway promotes terminal differentiation of T cells and loss of memory, which affects T cell function [ 33 ].…”
Section: Strategy For Optimizing Metabolism To Improve Efficacy During Car-t Cells Productionmentioning
confidence: 99%
“…Cell migration [ 28 30 , 39 , 40 , 43 ] was assayed using a transwell chamber (Corning, New York, USA). The EPCs after 7 days of culture were seeded in the upper chambers at a density of 4 × 10 4 cells per well, while 500 μl medium was added to the lower chamber.…”
Section: Methodsmentioning
confidence: 99%
“… 39 Accumulating evidence both in vitro and in vivo has indicated that PI3K signaling is a critical factor for driving M2 polarization and M2-like TAMs-induced tumor cell invasion. 40 Among the PI3K families, PI3Kγ has been found to be involved in various steps of macrophage activation and function. 41 Inhibition of PI3Kγ can block the immunosuppressive effects of TAMs, enhancing the activation of cluster of CD8 + T cells and responses to immune checkpoint inhibitors.…”
Section: Trends In Clinical Trials According To Different Mechanismsmentioning
confidence: 99%